심방세동 환자의 심율동전환 시행 전·후 warfarin 치료의 적절성 평가 - 문정연; 김보람; 조은정; 조윤숙; 한현주; 최의근; Moon, Jung-Yeon; Kim, Bo-Ram; Jo, Eun-Jung; Cho, Yoon-Sook; Han, Hyun-Joo; Choi, Eue-Keun (한국임상약학회지, 2016)
Objective: Direct current cardioversion for atrial fibrillation could be associated with the risk of thromboembolic events. Anticoagulation therapy with warfarin (INR 2.0-3.0) is recommended 3 weeks before and 4 weeks after cardioversion to reduce the risk of thromboembolism. This study evaluated warfarin therapy in pharmacist-managed anticoagulant services (ACS). Methods: This retrospective study was performed in 106 patients with atrial fibrillation from 2012 to 2013. The primary efficacy endpoint was the composite of stroke, transient ischemic attack, myocardial infarction, and cardiovascular death. The primary safety measure was major bleeding. To evaluate the peri-procedural effects of warfarin treatment, we studied whether target INR was maintained, as well as the maintenance period of the therapeutic range. Quality of treatment was measured by time in therapeutic range (TTR) by using the Rosendaal method. Results: There were no thromboembolic events, but TEE examination at time of cardioversion showed a left atrial thrombus in three patients (2.8%). Bleeding complications after cardioversion occurred in 2 patients (1.9%). The average INR value at the time of cardioversion was $2.59{±}0.8$, and was within the therapeutic range in 83 patients (78%). Analysis of the patients in whom the value was within the therapeutic range twice consecutively showed that the ratio of TTR was 80% and the therapeutic range was maintained in 67 patients (63%) for an average of 4.90 weeks prior to cardioversion. Similarly, 76 patients (72%) had a stable INR within the therapeutic range for an average of 5.70 weeks and a mean TTR of 83%. Conclusion: Pharmacists significantly contributed to appropriate warfarin treatment with close monitoring during cardioversion. Likewise, active pharmacist monitoring and systemic management should be considered to reduce thromboembolism and bleeding complications in the peri-cardioversion period.